Impact of metal/ceramic interactions on interfacial shear strength: Study of Cr/TiN using a new modified embedded-atom potential. (15th November 2021) - Dhariwal, Nisha; Miraz, Abu Shama Mohammad; Meng, W.J.; Ramachandran, Bala R.; Wick, Collin D.
Graphical abstract: Highlights: Modified embedded atom method interatomic potential model for Cr/TiN. Generalized stacking fault energy is directly related to shear strength. The maximum shear stress of 7.2 GPa was observed Cr/TiN. Stronger interactions and better lattice matching led to higher shear strength. Cr metal is stronger than Cu and Ti with nitrides, in agreement with experiment. Abstract: The effect of misfit dislocation networks (MDNs) on the stability and shear strength of Cr/TiN was investigated using a newly developed modified embedded atom model parameterized to pure Cr, CrTi, CrN, and Cr/TiN interfacial properties. The interfacial energy was lowest when the MDN was located in the Cr layer adjacent to the chemical interface, which also had the largest dislocation core widths. This was consistent with generalized stacking fault energies, which had lower energy barriers between the first and second Cr layers next to the chemical interface. As the MDN moved away from the interface, dislocation core widths consistently decreased along with the interfacial energy. For all positions of MDNs, shear failure occurred in the ceramic, between the first and second TiN layers next to the chemical interface. The lowest shear strength was found for the system with the MDN in the first Cr layer with respect to the chemical interface. Only for this particular configuration was there a significant plastic deformation present.